Intralesional Rituximab for the Treatment of Recurrent Ocular Adnexal Lymphoma. (May 2017) - Demirci, Hakan; Kauh, Courtney Y.; Rajaii, Fatemeh; Elner, Victor M.
Abstract : A 41-year-old female with Sjogren syndrome presented with a 5-month history of bilateral upper eyelid swelling. Incisional biopsy of the left lacrimal gland revealed mucosa-associated lymphoid tissue lymphoma. Due to bilateral severe dry eyes, the patient declined external beam radiotherapy and systemic rituximab was initiated. The patient responded well to intravenous rituximab and the follow-up CT revealed decrease in size of both lacrimal glands. Eleven months after systemic rituximab, the patient developed bilateral lacrimal gland recurrence. The patient declined external beam radiotherapy. Intralesional rituximab (50 mg/1 ml) was injected into the left lacrimal gland, followed by injection in the right lacrimal gland 7 months later. Twenty-three months follow-up after the injection into the right lacrimal gland, there was significant decrease in size of bilateral lacrimal glands and subjective improvement of dry eye symptoms. This case highlights the intralesional rituximab as an alternative therapy for recurrent orbital mucosa-associated lymphoid tissue lymphoma in selected cases. Abstract : Intralesional Rituximab injection might be an alternative therapy for recurrent ocular adnexal mucosa-associated lymphoid tissue (MALT) lymphoma.